Devaneios da fogueira : os saberes populares associados ao fogo atiçam diálogos de educação ambiental sobre incêndios florestais, crise climática e bem viver - Bertier, Flavia Lopes (2020)
The Climate Justice and Environmental Education International Network (REAJA) studies how the climate crisis affects the whole planet, being most strongly felt in social groups in vulnerable situations. In Brazil, wildfires are one of the factors that contribute to the emission of greenhouse gases (GHG) in the atmosphere, accelerating the climate colapse. The “Zero Fire” policy adopted by the Brazilian government is responsible for the increase of wildfires in the Cerrado, because it doesn’t consider that the biome is fire dependent, where this element is not a disturbance, but a fator essential for the preservation of its ecological processes. The exclusion of fire in the Cerrado causes accumulation of organic substances in extensive areas and facilitates the spread of large-scale fires in dry seasons, which indiscriminately affect protected and private areas with huge losses of biodiversity, socioeconomic impacts and GHG emissions. Several studies indicate that traditional populations of the Cerrado use fire without harming nature, as they depend on it. To identify fire practices, techniques, values and cultures, the Environmental Education Researcher Group (GPEA) of the Mato Grosso Federal University (UFMT), a member of REAJA, developed the social mapping of the popular knowledge associated with fire in the rural communities of São Jerônimo (Cuiabá/MT) and Água Fria (Chapada dos Guimarães/MT), located around the Chapada dos Guimarães National Park (PNCG). The Social Map methodology was chosen to give visibility to this knowledge, in disuse by the communities for fearing government sanctions. Knowing such knowledge is a key fator to implement the Integrated Fire Management (MIF) actions in the PNCG. As a result, this Master degree in Education dissertation presents the relationship between everyday practices and the traditional knowledge of using fire with the cycles of nature, how fire creates and strengthens community bonds and how participates in the environmental conservancy. The dialogues present in the activities of the Social Map, permeated by issues related to fire, stimulate dialogicity, reveal values, beliefs, ethics and political perspective inherent to GPEA environmental education. With “sensitive listening” aproach during workshops, collective mapping meetings and interviews with community elders, the participants' impressions about the relationship between wildfires, the climate crisis and their Well Living are identified. The reports are interpreted based on Gaston Bachelard's Phenomenology and reveal the interwoven dualities of fire: good and bad. The joint elaboration of the Social Map of popular knowledge associated to fire reveals latent environmental needs and problems. The light that emerges from dialogues and collective experiences reflects the realities experienced by the research participants and unravels possibilities for public policies that can be applied beyond the boundaries of the PNCG. This “Knowledge Symbiosis” contributes to the reduction of wildfires, strengthens communities and helps to decriminalize the traditional use of fire in the Cerrado of Mato Grosso.